Kajian Maslahah Pada Pemanfaatan Sumber Daya Air Pada Usaha Air Minum Dalam Kemasan Milik Pesantren Bustanul Ulum Pragaan Di Sumenep - Faekarotul Mufidah Al-Anshori; Muttaqin Choiri (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
This research analyzes the application of maslahah in the utilization of Water Resources (SDA) in the packaged drinking water (AMDK) business owned by Bustanul Ulum Pragaan Islamic Boarding School, Sumenep. This business contributes economically to the Islamic boarding schools and the community by creating job opportunities and playing a role in providing clean and quality drinking water. The type of research is field research using a qualitative approach. The data sources used are primary and secondary data sources. Data collection techniques include interviews, observations, and documentation. The research results show that the benefits obtained from the utilization of natural resources by the AMDK Chellep business are considered maslahah al-hajjiyah, because although it is not a basic necessity, this product facilitates the community's access to clean water. This business also considers sustainability aspects, such as waste management used by residents for daily needs and irrigation. The management of natural resources is carried out with official permission so as not to disrupt residents' access to water sources. In conclusion, the utilization of natural resources in this bottled water business not only has a positive economic impact on the Islamic boarding schools but also provides significant social contributions that align with Islamic principles. Keywords: Maslahah, Utilization of Water Resouces, Bottled Dringking Water, Islamic Boarding School